Exploring Therapeutic Sailing as an Intervention for the Veteran Population - Culbreth, Lilly A (My University, 2024)
Therapeutic sailing is an intervention used in recreational therapy, or therapeutic recreation to improve quality of life in the physical, psychological, social, and emotional domains. While participation in therapeutic sailing by people with disabilities is regarded to have positive outcomes on quality of life, evidence based research is still lacking. Veterans are a unique population in which they tend to need treatment for a range of conditions; such as post-traumatic stress disorder (PTSD), depression, anxiety, and physical disabilities. Therapeutic sailing as a modality leverages the unique environment of the water, combined with the physical and cognitive challenges of sailing to promote emotional well-being, self-esteem, self-efficacy, and improved social connection by mindfulness. The connection to nature provides opportunity for stress relief and emotional regulation. Additionally, physical activity on the water improves mobility, strength, and endurance. This literature review analyzes whether therapeutic sailing is an adequate form of treatment for the Veteran population.
Keywords: recreational therapy; sailing; therapeutic sailing; veterans; psychological; physical; PTSD; substance abuse